Beginning CSharp 2008 Databases - Agarwal, Vidya Vrat (Apress, 2012)
Because most real-world applications interact with data stored in relational databases, every C# programmer needs to know how to access that data. This book specifically covers how to interact with the SQL Server 2005 database using C# 2008. This book also covers LINQ and ADO.NET 3.5, the most exciting features of .NET Framework 3.5. The chapters that shed light on database concepts will help you understand those concepts better than you would have learning them from a pure database concepts book. We also cover many new features of T-SQL, which SQL Server 2005 now incorporates. This book has been written in such a way that beginners will easily understand the text and even professionals will benefit from the instruction within. If you want to use Visual Studio 2008 to build database applications, this is the right book for you; the text will not only walk you through all the concepts that an application developer may have to use, but also explain each piece of code you will write for example applications. The chapters in this book are organized in such a manner that you will build a strong foundation before moving on to more advanced techniques.